1H nuclear magnetic resonance study of low-temperature water dynamics in a water-soaked perfluorosulfonic acid ionomer Nafion film. (January 2017) - Han, Jun Hee; Lee, Kyu Won; Lee, Cheol Eui
Abstract: We have employed proton nuclear magnetic resonance (NMR) spectroscopy in order to study the low-temperature water dynamics in a water-soaked perfluorosulfonic acid ionomer Nafion (NR-211) film. According to the recent models, Nafion may comprise water strongly bound to the sulfonic acid group, hydration water, and condensed water species. In this work, three separate NMR peaks from the water species revealing distinct behaviors were identified. A significant portion of the "bound" water remained unfrozen down to 200 K, whereas a slow-to-fast motional limit transition was observed at T M =220 K from the relaxation measurements. Abstract : Highlights: Proton NMR to study the low-temperature water dynamics in a water-soaked Nafion film. Three distinct water species were well separated revealing distinct behaviors. "Bound" water remained unfrozen showing a slow-to-fast motional limit transition at 220 K.